x+y=5,xy=6,求x(x+y)×(x-y)-x(x+y)2

来源:学生作业帮助网 编辑:作业帮 时间:2022/09/27 18:04:24
x+y=5,xy=6,求x(x+y)×(x-y)-x(x+y)2
若(x*x+y*y)(x*x+y*y)-4x*x*y*y=0,求代数式(x*x+5xy+y*y)/(x*x+2xy+y*y)的值

若(x*x+y*y)(x*x+y*y)-4x*x*y*y=0,求代数式(x*x+5xy+y*y)/(x*x+2xy+y*y)的值若(x*x+y*y)(x*x+y*y)-4x*x*y*y=0,求代数式(

f(x+y,x-y)=(x^2-y^2)/2xy,求f(x,y)!

f(x+y,x-y)=(x^2-y^2)/2xy,求f(x,y)!f(x+y,x-y)=(x^2-y^2)/2xy,求f(x,y)!f(x+y,x-y)=(x^2-y^2)/2xy,求f(x,y)!1

正数x,y满足x-y=2xy,求x-y/x+y的值.

正数x,y满足x-y=2xy,求x-y/x+y的值.正数x,y满足x-y=2xy,求x-y/x+y的值.正数x,y满足x-y=2xy,求x-y/x+y的值.

f(x+y,x-y)=2xy(x-y),求f(x,y)

f(x+y,x-y)=2xy(x-y),求f(x,y)f(x+y,x-y)=2xy(x-y),求f(x,y)f(x+y,x-y)=2xy(x-y),求f(x,y)f(x+y,x-y)=(1/2)[(x

|x|/x+y/|y|+xy/|xy|=

|x|/x+y/|y|+xy/|xy|=|x|/x+y/|y|+xy/|xy|=|x|/x+y/|y|+xy/|xy|=由题可知x,y都不等于0.下面分x>0,y>0x>0yx0x四种情况去绝对值,这

已知x*x-4xy+4y*y=0 求[2x(x+y)-y(x+y)]/(4x*x-4xy+y*y)的值?

已知x*x-4xy+4y*y=0求[2x(x+y)-y(x+y)]/(4x*x-4xy+y*y)的值?已知x*x-4xy+4y*y=0求[2x(x+y)-y(x+y)]/(4x*x-4xy+y*y)的

1/x-1/y=x,求5y+xy-5y/y-xy-x=?

1/x-1/y=x,求5y+xy-5y/y-xy-x=?1/x-1/y=x,求5y+xy-5y/y-xy-x=?1/x-1/y=x,求5y+xy-5y/y-xy-x=?5y+xy-5y/y-xy-x(

已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y

已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2

f(x,y)=xy+e^x x arctanx/y ,求f(x+y,x-y)

f(x,y)=xy+e^xxarctanx/y,求f(x+y,x-y)f(x,y)=xy+e^xxarctanx/y,求f(x+y,x-y)f(x,y)=xy+e^xxarctanx/y,求f(x+y

已知x+y=-1,xy=-2,求代数式-5(x+y)+(x-y)+x(xy+y)的值

已知x+y=-1,xy=-2,求代数式-5(x+y)+(x-y)+x(xy+y)的值已知x+y=-1,xy=-2,求代数式-5(x+y)+(x-y)+x(xy+y)的值已知x+y=-1,xy=-2,求

√x(√x+2√y)=√y(6√x+5√y,求x-3√xy+2y/x+√xy-6y

√x(√x+2√y)=√y(6√x+5√y,求x-3√xy+2y/x+√xy-6y√x(√x+2√y)=√y(6√x+5√y,求x-3√xy+2y/x+√xy-6y√x(√x+2√y)=√y(6√x+

∫x(∫x+2∫y)=∫y(6∫x+5∫y),求:(x+∫xy-y)/(2x+∫xy+3y)

∫x(∫x+2∫y)=∫y(6∫x+5∫y),求:(x+∫xy-y)/(2x+∫xy+3y)∫x(∫x+2∫y)=∫y(6∫x+5∫y),求:(x+∫xy-y)/(2x+∫xy+3y)∫x(∫x+2∫

已知x+y=6,xy=7,试求x*x+y*y,x*x-y*y的值

已知x+y=6,xy=7,试求x*x+y*y,x*x-y*y的值已知x+y=6,xy=7,试求x*x+y*y,x*x-y*y的值已知x+y=6,xy=7,试求x*x+y*y,x*x-y*y的值x

已知x+y=-5,x*x+y*y=19求xy和(x-y)*(x-y)的值

已知x+y=-5,x*x+y*y=19求xy和(x-y)*(x-y)的值已知x+y=-5,x*x+y*y=19求xy和(x-y)*(x-y)的值已知x+y=-5,x*x+y*y=19求xy和(x-y)

f(x^2-y^2,x-y)=x+y+x^2-xy,求f'(x,y)对y求导

f(x^2-y^2,x-y)=x+y+x^2-xy,求f''(x,y)对y求导f(x^2-y^2,x-y)=x+y+x^2-xy,求f''(x,y)对y求导f(x^2-y^2,x-y)=x+y+x^2-x

已知x/y=2,求2x(x+y)-y(x+y)/4x²-4xy+y²

已知x/y=2,求2x(x+y)-y(x+y)/4x²-4xy+y²已知x/y=2,求2x(x+y)-y(x+y)/4x²-4xy+y²已知x/y=2,求2x(

x+y=1,xy=-1/2,求x(x+y)(x-y)-x(x+y)2

x+y=1,xy=-1/2,求x(x+y)(x-y)-x(x+y)2x+y=1,xy=-1/2,求x(x+y)(x-y)-x(x+y)2x+y=1,xy=-1/2,求x(x+y)(x-y)-x(x+y

诺x+y=6,xy=4 求(5x-4y-3xy)-(8x-y+2xy)

诺x+y=6,xy=4求(5x-4y-3xy)-(8x-y+2xy)诺x+y=6,xy=4求(5x-4y-3xy)-(8x-y+2xy)诺x+y=6,xy=4求(5x-4y-3xy)-(8x-y+2x

2x^+xy-y^-4x+5y-6=?

2x^+xy-y^-4x+5y-6=?2x^+xy-y^-4x+5y-6=?2x^+xy-y^-4x+5y-6=?原式=(2x-y)(x+y)-4x+5y-6=(2x-y)(x+y)+(2x+2y)-

sin(x*x+y)=xy 求y'x

sin(x*x+y)=xy求y''xsin(x*x+y)=xy求y''xsin(x*x+y)=xy求y''xy''x是对y求关于x的导数吧?两边求导:cos(x*x+y)*(2*x+y'')=y+xy''所以y''